Livelihood Status and Usage of Nutrition-Sensitive Advisory Services among Rural Farming Households in Kwara State, Nigeria - Akinrinde, Adeniyi; Omotesho, Kemi Funmilayo (Jordan Journal of Agricultural Sciences, 2025)
Good nutrition strengthens the immune system and reduces disease risks. In Nigeria, malnutrition is prevalent in rural agrarian areas. Despite deploying Nutrition-Sensitive Advisory Services, statistics show no significant improvement. The objectives of the study were to examine the livelihood status of rural farming households, assess the extent of use of Nutrition-Sensitive Advisory Services, analyze the relationship between livelihood status and use of Nutrition-Sensitive Advisory Services, and identify constraints to the use of Nutrition-Sensitive Advisory Services. Using a three-stage sampling procedure, 390 households were selected from a population of 177,260 rural farming households where Nutrition-Sensitive Advisory Services had been disseminated. Data were collected using an interview schedule and analyzed using frequency counts, percentages, standard deviation, and Pearson’s Product-Moment Correlation Analysis. Findings indicated that rural farming households had a moderate livelihood status (Mean Livelihood Sustainability Index = 0.57), poor use of Nutrition-Sensitive Advisory Services (x̄ = 0.47), and a positive correlation between livelihood status and use of Nutrition-Sensitive Advisory Services (r = 0.830, p≤0.05). Major constraints to use of Nutrition-Sensitive Advisory Services were unaffordability of food varieties (x̄ = 2.55), poor availability of food varieties (x̄ = 2.23), and poor follow-up by extension workers (x̄ = 2.20). The study concluded that although livelihood status was moderate, use of Nutrition-Sensitive Advisory Services was poor and could be improved by enhancing livelihood capitals. A multi-dimensional approach to improving rural farming households’ livelihood status was recommended.